A voyage long and strange : rediscovering the new world - Horwitz, Tony, 1958-2019- (Henry Holt and Co., 2008)
An irresistible blend of history, myth, and misadventure, "A Voyage Long and Strange" captures the wonder and drama of first contact. Vikings, conquistadors, French voyageurs--these and many others roamed an unknown continent in quest of grapes, gold, converts, even a cure for syphilis. Though most failed, their remarkable exploits left an enduring mark on the land and people encountered by late-arriving English settlers.--From publisher description.